Establishing a minimum PMI for bone sun bleaching in a UK environment with a controlled desert-simulated comparison - Stokes, Sarah; Márquez-Grant, Nicholas; Greenwood, Charlene (Springer, 2020)
Microenvironments play a significant part in understanding the post-mortem interval in forensic taphonomy. Recently, the value of weathering factors in relation to obtaining a PMI has been investigated further. In this study, observations were made to calculate the length of time it takes for three different bone elements (femur, rib, and scapula) to bleach in a UK summer and winter. This research also investigated whether there were any physicochemical modifications to the bone caused by bleaching. Porcine femora, scapulae, and ribs were placed into open and shaded areas of an outdoor research facility located in Oxfordshire, UK, during summer (July–Sep) and winter months (Dec–Mar). The specimens were monitored at 3-week intervals using photography, and an observational scoring method was developed to quantify the extent of bleaching. As temperatures are typically much lower in the UK compared with warmer climates, a controlled indoor-simulated desert experiment was also undertaken to be used as a control. This allowed sun bleaching and changes to the bone chemistry to be monitored in a controlled, high-UV environment for comparison with the UK outdoor experiments. Fourier transform infrared spectroscopy (FTIR) was employed to analyze physicochemical modifications to both the mineral and organic components of the bone. The FTIR was used to calculate crystallinity index (CI), mineral to organic ratio, and the relative amount of carbonate concentrations. Weather data was collected and a positive correlation was found between both ultraviolet (UV) levels and accumulated degree days (ADD) when compared with observational bleaching scores. Bleaching (whitening) of the bone samples occurred in both seasons but at different rates, with the bleaching process occurring at a slower rate in winter. During summer, the initial bleaching process was evident at 6 weeks, and by 9 weeks, the bones were an off-white colour. During the winter period, whitening of the bone started at 9 weeks; however, only the scapula and rib samples displayed a similar off-white colour. This colouration was observed at 13 weeks rather than at 9 weeks. The desert simulation samples started bleaching in a similar pattern to the outdoor samples after 1 week but the bones did not fully bleach. The bone chemistry, based on physicochemical properties obtained from the FTIR, showed a significant statistical difference between the simulated desert and winter season when compared against a control sample. For the winter samples, the mineral to organic ratio was significantly higher than that in the control, suggesting a reduction in the proportion of organic. For the samples in the simulated desert environment, the crystallinity index was significantly higher than that in the control samples, suggesting an increase in crystallinity. The results of this experiment support the fact that it is possible to achieve bleaching in a UK environment and that the minimal time frame for this to occur differs in seasons.
Keywords: Forensic taphonomy; Forensic anthropology; Bone bleaching; FTIR; Bone weathering